2019
DOI: 10.1016/j.jpeds.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Weight Outcomes, Co-Occurring Conditions, and Severity of Autism Spectrum Disorder in the Study to Explore Early Development

Abstract: Objective-To assess contributing factors to increased obesity risk, by comparing children with autism spectrum disorder (ASD), developmental delays/disorders, and general population controls in weight status, and to examine associations between weight status and presence of co-occurring medical, behavioral, developmental, or psychiatric conditions across groups and ASD severity among children with ASD. Study design-The Study to Explore Early Development is a multisite cross-sectional study of children, 2-5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 39 publications
1
28
0
16
Order By: Relevance
“…Several studies have indicated that the prevalence of overweight and obesity is high in autistic children and adolescents (Curtin et al 2005;Xiong et al 2009;Curtin et al 2010;Broder-Fingert et al 2014;Corvey et al 2016;Granich et al 2016;Healy et al 2019;Levy et al 2019).…”
Section: Weight Status Of Individuals With Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that the prevalence of overweight and obesity is high in autistic children and adolescents (Curtin et al 2005;Xiong et al 2009;Curtin et al 2010;Broder-Fingert et al 2014;Corvey et al 2016;Granich et al 2016;Healy et al 2019;Levy et al 2019).…”
Section: Weight Status Of Individuals With Asdmentioning
confidence: 99%
“…Data coming from epidemiologic studies suggest that short sleep duration is associated with weight gain (Chen et al 2008). Sleep disturbances are frequent in children with ASD and can occur in 52.0-73.0% individuals with ASD (Levy et al, 2019;Curtin 2014). The spectrum of sleep disturbances observed in children with ASD includes bedtime resistance problems, insomnia, parasomnias, sleep disordered breathing, morning arising problems, and daytime sleepiness (Devnani and Hegde 2015).…”
Section: Sleep Disturbancesmentioning
confidence: 99%
“…Bandini et al (2015) found that children with DD are 27-59% more likely to develop obesity than typically developing (TD) peers with differences depending on national survey instrument and type of disability. According to the National Survey of Children's Health (2017-2018, the prevalence of obesity in U.S. youth ages 10 to 17 is 14.0% but 19.5% among children with DD. No national data are available for obesity prevalence among children with DD ages 0-5 years; however, the incidence of overall childhood obesity is highest in ages 2-5 years (Cheung, Cunningham, Narayan, & Kramer, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Effective intervention for change-resistant behavior is important because life can be unpredictable, preventing change is nearly impossible, and change-resistant behavior can have significant short-and long-term negative consequences (Fisher et al, 2019;Flygare Wallén et al, 2018;Freedman et al, 1999;Kamal Nor et al, 2019;Levy et al, 2019). Children with autism frequently demonstrate change-resistant behavior at mealtime, such as insistence on eating the same few unhealthy foods or engaging in rigid mealtime routines (Bandini et al, 2010;Cermak et al, 2010;Heifert et al, 2016;Levin & Carr, 2001;Postorino et al, 2015;Schreck & Williams, 2006;Sharp et al, 2018;Silbaugh et al, 2018).…”
mentioning
confidence: 99%
“…Selective diets with poor nutritional content can cause further impairments in behavioral and cognitive functioning, and unhealthy weight gain, which increases the risk for severe health problems (e.g., obesity, Type-2 diabetes, and hypertension; Freedman et al, 1999;Ludwig et al, 1999). In fact, the prevalence of obesity and diabetes among individuals with autism, and the prevalence of hypertension in males with autism is higher than that of typically developing peers, which is alarming given the significant negative health consequences of these diseases (Flygare Wallén et al, 2018;Levy et al, 2019). Children with autism and change-resistant feeding behavior may also engage in inappropriate mealtime behavior (e.g., aggression, crying, pushing food away, self-injury, spitting food out, and vomiting), which may discourage the caregiver from attempting to change the child's diet (Borrero et al, 2016;Borrero et al, 2010;Piazza, Fisher et al, 2003).…”
mentioning
confidence: 99%